2021
DOI: 10.1016/j.fishres.2021.105961
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 restrictions and recreational fisheries in Ontario, Canada: Preliminary insights from an online angler survey

Abstract: The COVID-19 pandemic and corresponding public health mitigation strategies have altered many facets of human life. And yet, little is known about how public health measures have impacted complex socio-ecological systems such as recreational fisheries. Using a web-based online snowball survey, we targeted resident anglers in Ontario, Canada, to obtain preliminary insight on how the pandemic has impacted recreational fishing and related activity. We also explored angler perspectives on pandemic-related restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 55 publications
6
34
2
1
Order By: Relevance
“…As a result of restrictions affecting access to the fishery, recreational fishers in general, and especially advanced fishers, showed lower physical activity and lower fish consumption. Recent studies on the impacts of the COVID-19 pandemic on different recreational activities also showed results like those found in our study; e.g., Howarth et al (2021) noted that fish consumption was lower among recreational fishers during the pandemic, while Curtis et al (2021) concluded that the physical activity of the population decreased. Consequently, it is not surprising that the fishers surveyed in this study reported poor night rest, worse mood, and concerns about their health condition, especially in the case of advanced fishers.…”
Section: Global Importancesupporting
confidence: 88%
See 1 more Smart Citation
“…As a result of restrictions affecting access to the fishery, recreational fishers in general, and especially advanced fishers, showed lower physical activity and lower fish consumption. Recent studies on the impacts of the COVID-19 pandemic on different recreational activities also showed results like those found in our study; e.g., Howarth et al (2021) noted that fish consumption was lower among recreational fishers during the pandemic, while Curtis et al (2021) concluded that the physical activity of the population decreased. Consequently, it is not surprising that the fishers surveyed in this study reported poor night rest, worse mood, and concerns about their health condition, especially in the case of advanced fishers.…”
Section: Global Importancesupporting
confidence: 88%
“…Individual outdoor leisure activities facilitate social distancing and indirectly mitigate the spread of COVID-19 (Güzel et al, 2020), especially when practiced in natural areas (Venter et al, 2020). In this work, as also found by other authors (e.g., Howarth et al, 2021), we show that the practice of marine recreational fishing improves the perceived health and wellbeing of the population during a pandemic. Allowing access of marine recreational fishers would significantly contribute to reducing important socioeconomic impacts, especially on the most vulnerable population groups.…”
Section: Governing Marine Recreational Fishing In Future Pandemicssupporting
confidence: 87%
“…The impact of the pandemic on outdoor recreation globally has been substantial. Across the world, government restrictions on activity and movement such as social distancing requirements, border closures and stay-at-home orders have limited citizens’ opportunities to interact with others and the world around them ( Geng, Innes, Wu, & Wang, 2021 ; Howarth et al, 2021 ). Recent studies on how COVID-19 pandemics induce recreation coping strategies have documented change in recreation patterns that includes change of frequency, activity types, activity settings and distances travelled to recreate (Humagain & Singleton, 2021; Kane, Zajchowski, Allen, McLeod, & Allen, 2021; Sivan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite restrictions on activity and movement, there is evidence in the literature that outdoor recreation activity may have actually increased during lockdown measures related to COVID-19 ( Derks, Giessen, & Winkel, 2020 ; Geng et al, 2021 ; Korpilo et al, 2021 ; London Legacy Development Corporation, 2020 ). A number of studies in Europe, the United States and Canada have investigated outdoor recreation, physical activity and park visitation in and around periods of restriction due to COVID-19 ( London Legacy Development Corporation, 2020 ; Derks et al, 2020 ; Geng et al, 2021 ; Howarth et al, 2021 ; Landry, Bergstrom, Salazar, & Turner, 2021 ; Lesser & Nienhuis, 2020 ; London Legacy Development; Rice et al, 2020 ). One study of a forest park in Germany found that during a period of lockdown, visitor numbers more than doubled the previous daily record ( Derks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation